2021
DOI: 10.3758/s13423-021-02006-8
|View full text |Cite
|
Sign up to set email alerts
|

Perceived depth modulates perceptual resolution

Abstract: We thank Johnathan Tong for his guidance in data analysis and Krista Chiasson for her help in data collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
0
7
1
Order By: Relevance
“…Importantly, since visual search performance at baseline (i.e., before training) was not significantly different whether carried out in the near or far space, the effect we newly report here cannot be ascribed to a general difference in performance in the two spaces. Overall, these results are at odds with previous work on visual perception where an advantage for the processing of stimuli in the near compared to the far space have been recently documented (Ahsan et al, 2021(Ahsan et al, , 2022Blini et al, 2018;Dureux et al, 2021). In the following, we consider several factors that can potentially determine the unexpected far space advantage in perceptual learning.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Importantly, since visual search performance at baseline (i.e., before training) was not significantly different whether carried out in the near or far space, the effect we newly report here cannot be ascribed to a general difference in performance in the two spaces. Overall, these results are at odds with previous work on visual perception where an advantage for the processing of stimuli in the near compared to the far space have been recently documented (Ahsan et al, 2021(Ahsan et al, , 2022Blini et al, 2018;Dureux et al, 2021). In the following, we consider several factors that can potentially determine the unexpected far space advantage in perceptual learning.…”
Section: Discussionmentioning
confidence: 56%
“…Performance was assessed both before and after a training session in which participants were trained by repeated blocks of the visual search task, either in PPS or EPS, looking only for one specific orientation. Based on the previous studies showing a PPS advantage for visual processing (Ahsan et al, 2021;Blini et al, 2018;Zanini et al, 2021), we predicted to observe a larger improvement in performance for participants who trained in the near compared to the far space, but only for the trained orientation (Sigman & Gilbert, 2000). Moreover, owing to the previously documented degree of topological specificity of the improvement (Sigman & Gilbert, 2000), we additionally predicted the benefit following the near space training to be specific for the PPS.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Some results seem to indicate that this transfer is not justified. In particular, it has been observed that performance in some perceptual tasks is better for objects that appear closer (and smaller) than for those that appear further away (and larger; Ahsan et al, 2022; Blini et al, 2018). This finding appears to contradict our claim that higher spatial resolution leads to larger apparent size.…”
Section: Discussionmentioning
confidence: 99%
“…As noted in the Introduction, previous studies on target discrimination that have examined the effect of depth have revealed both near-and far advantages. In Experiments 4A and 4B, we adopted a modified discrimination task from an empirical study that investigated peripheral target discrimination across near/far depth, and that produced a near advantage 36 . Our aim was to gain an understanding of why such a method produces a near advantage whereas our method here produced a far advantage.…”
Section: Methodsmentioning
confidence: 99%